2017
DOI: 10.1093/hmg/ddx057
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1 mutations found in HSANIE patients affect interaction with UHRF1 and neuronal differentiation

Abstract: DNMT1 is recruited to substrate sites by PCNA and UHRF1 to maintain DNA methylation after replication. The cell cycle dependent recruitment of DNMT1 is mediated by the PCNA-binding domain (PBD) and the targeting sequence (TS) within the N-terminal regulatory domain. The TS domain was found to be mutated in patients suffering from hereditary sensory and autonomic neuropathies with dementia and hearing loss (HSANIE) and autosomal dominant cerebellar ataxia deafness and narcolepsy (ADCA-DN) and is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 74 publications
2
41
0
2
Order By: Relevance
“…dnmt1 is expressed in RSCs at 4dpf ( Figure 4I,J), consistent with dnmt1's known requirements in stem cell populations in vivo 27,30,31,50,51 . Loss of Dnmt1 function results in aberrant gene expression in a number of contexts 45,50,52,53 and therefore we wanted to determine if CMZ-specific gene expression was altered in the dnmt1 -/-CMZ. Previous reports have characterized the expression/distribution of the CMZ-specific genes: col15a1b, cyclinD1, cdkn1c, and atoh7 14,15,54 .…”
Section: Cell Death Is Elevated In the Dnmt1 -/-Cmz In A P53-independmentioning
confidence: 99%
“…dnmt1 is expressed in RSCs at 4dpf ( Figure 4I,J), consistent with dnmt1's known requirements in stem cell populations in vivo 27,30,31,50,51 . Loss of Dnmt1 function results in aberrant gene expression in a number of contexts 45,50,52,53 and therefore we wanted to determine if CMZ-specific gene expression was altered in the dnmt1 -/-CMZ. Previous reports have characterized the expression/distribution of the CMZ-specific genes: col15a1b, cyclinD1, cdkn1c, and atoh7 14,15,54 .…”
Section: Cell Death Is Elevated In the Dnmt1 -/-Cmz In A P53-independmentioning
confidence: 99%
“…A recently published study investigating mutations in exon 20 found that these mutations affect DNMT1 interaction with the essential cofactor UHRF1 (ubiquitin-like with PHD and ring finger domains 1), which is believed to cause cell cycle-dependent degradation of DNMT1 and lead to impaired neuronal differentiation [7]. Further studies reporting different cohorts with a variety of mutations in DNMT1 need to be published to further understand the pathogenic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, DNMT1 is recruited to DNA by its obligate partner UHRF1 (ubiquitin‐like, containing PHD and RING finger domains 1) throughout S phase, an interaction suggested as promoting conformational changes and the unmasking of the DNMT1 catalytic domain . Indeed, HSAN1E mutations in the RFTS domain reproduced in the mouse disrupt the Dnmt1/Uhrf1 interaction, affect DNMT1's proper folding, and cause a cell cycle‐dependent degradation of Dnmt1that results in defective DNAme maintenance . They also affect the sub‐cellular localization of DNMT1 in neurons, promoting its translocation to the cytoplasm and preventing its interaction with DNA.…”
Section: Mutations In Dna Methyltransferases: Direct Impact On Dna Mementioning
confidence: 99%